Avaliação de biodigestor tubular na degradação anaeróbia de cama de frango de corte - Alcantara, Michael Steinhorst (2012)
In the twenty-first century, the broiler production has increased in the world and continues increasing due to the high consumption of this meat. The broiler litter is the largest amount of waste generated in poultry production. It is also characterized by its high concentration of organic matter. The broiler production integrated system defines a radius around it to settle down poultry farms in order to reduce costs. It has also increased the concentration of broiler litter in the producing regions and demanded waste treatment. So, the anaerobic digestion has come as an alternative treatment with high organic load removal. Thus, this trial aimed at evaluating the treatment capacity of broiler litter by anaerobic digestion into tubular biodigester with a semi-continuous flow. The applied treatments varied both the amount of added total volatile solids, from 2.93 to 3.72%, as well as the hydraulic retention time, from 11.60 to 28.40 days. The digesters were maintained at 27 ºC and considered stabilized when the removal efficiency of total solids, total volatile solids and chemical oxygen demand were according to the statistical quality control. Once stabilized, the 11 digesters of 0.6 m per 0.15 m (length per diameter) were evaluated for removal of solids and chemical oxygen demand with statistical quality control and design composite central rotational in a factorial design (22), at two levels (-1, 1), plus the axial points (-α, α) and the central point. The analysis of statistical quality control showed that the treatment with 3.32% added total volatile solids and 20 days of hydraulic retention time removed the highest amount of total solids (64.37%) and total volatile solids (72.38%), while the removal values of chemical oxygen demand were similar in all treatments, around 80%. Significant statistical models were registered with the central composite rotational design to remove total solids and for chemical oxygen demand.